A micro-level investigation of the solid displacement method for porosity determination of dried food. (December 2015) - Joardder, Mohammad U.H.; Kumar, Chandan; Brown, Richard J.; Karim, M.A.
Highlights: Current porosity measurement using solid displacement method has been described. A micro level investigation was carried out to determine porosity measurements. Glass beads penetration into open and connected pores was found. Smaller glass beads was used to ensure high compactness and fluidity of it. Appropriate coating prior to porosity measurement is suggested to get better result. Abstract: Porosity is one of the key parameters of the macroscopic structure of porous media, generally defined as the ratio of the free spaces occupied (by the volume of air) within the material to the total volume of the material. Porosity is determined by measuring skeletal volume and the envelope volume. Solid displacement method is one of the inexpensive and easy methods to determine the envelope volume of a sample with an irregular shape. In this method, glass beads are used as a solid displacement media due to their uniform size, compactness and fluidity properties. The smaller size of the glass beads means that they enter into the open pores that have a larger diameter than the glass beads. Although extensive research has been carried out on porosity determination using displacement method, no study exists which adequately reports the micro-level observation of the sample during measurement. This study set out with the aim of assessing the accuracy of solid displacement method of bulk density measurement of dried foods by micro-level observation. Solid displacement method of porosity determination was conducted using a cylindrical vial (cylindrical plastic container) and 57 μm glass beads in order to measure the bulk density of apple slices at different moisture contents. A scanning electron microscope (SEM), a profilometer and Image J software were used to investigate the penetration of glass beads into the surface pores during the determination of the porosity of dried food. A helium pycnometer was used to measure the particle density of the sample. Results show that a significant number of pores were large enough to allow the glass beads to enter into the pores, thereby causing some erroneous results. It was also found that coating the dried sample with the appropriate coating material prior to measurement can resolve this problem.